REGENERATION OF ION-EXCHANGE CATALYST BY SUPERCRITICAL FLUID EXTRACTION PROCESS - M. R. Khazipov; K. A. Sagdeev; A. A. Sagdeev; A. T. Galimova; V. F. Khairutdinov; F. M. Gumerov (Известия высших учебных заведений: Проблемы энергетики)
Supercritical fluid extraction regeneration of the ion-exchange KU-2FPP catalyst is investigated. Results of change of mass of the catalyst are presented during regeneration at T = 383-393 K and P = 15-25 MPa and IR spectrums of chloroformic extracts of the studied catalyst samples. Results of the conducted researches allow to draw a conclusion on effective removal of polar and unpolar organic compounds. However the collateral reaction connected with emergence of dialkylphthalate is a probable cause of inefficiency of regeneration process with participation of SC-CO2 as the extractant. And use supercritical propane - butane mix (T = 393 K, P = 10-15 MPa) as the supercritical extractant allows to restore activity of the catalyst to the level meeting the requirements of industrial use.